(untitled) (Research, Society and Development, 2019)
Several studies in the literature have suggested the use of Information and Communication Technologies as teaching tools. Among these technologies are electronic educational games, which can also be used to encourage understanding of content covered in the classroom. Given these assertions, this research aimed to analyze educational games that address the theme of sanitation and how they can assist in the learning process. To this end, three didactic games were selected that were evaluated by a questionnaire regarding their technical and pedagogical aspects by teachers. Afterwards, these games were applied in four classes of elementary school in the sixth and seventh year, making a total of 74 students in two private schools in the municipalities of Mariana and Ouro Preto, Minas Gerais. Students involved in the activity also made their assessments after using the games: one in relation to the promoted interaction and the other related to the studied content. From the results it was observed that the technical aspects of the games were considered as “good” and “great”. In the conceptual assessment, performed before and after the use of games, students showed improvement in performance and this improvement was verified through the statistical analysis of the obtained data. From the statistical results it was verified that the improvement of the students’ performance in the content evaluation can be statistically attributed to the use of the games. Thus, it is concluded that there was a significant contribution of the use of educational games in the teaching and learning process for this experience in elementary school.